Psycho-pedagogical conditions of readiness of students to creative professional and educational activitie - Шепеленко, Тетяна; Пінська, Олена (Pedagogy of Higher and Secondary Education, 2014)
Shepelenko T. L.,Pinskауа A. L. Psycho-pedagogical conditions of readiness of students to creative professional and educational activitie. The article reveals the essence and features of professional-pedagogical creativity, students' willingness to creative teaching activity, there is characterized its structure (psychological, theoretical, practical readiness), there are covered the psychological and pedagogical conditions of formation in the educational process of higher education.